Three-dimensional channel design and fabrication in Polydimethylsiloxane (PDMS) elastomers using capillary action mechanism in fluidics for life sciences - Tijjani Adam, Shuwa; Uda, Hashim, Prof. Dr. (AENSI Publications, 2013)
link to publisher's homepage at http://www.aensiweb.com/